Theoretical investigation of structural, electronic, mechanical, surface work function and thermodynamic properties of La1-xMxB6 (M = Ba, Sr, Ca) compounds: Potential plasma grid materials in N-NBI system - Jun Hu; Xin Zhang; Yuhong Xu; Guangjiu Lei; Sanqiu Liu; Katsuyoshi Tsumori; Haruhisa Nakano; Masaki Osakabe; Mitsutaka Isobe; Shoichi Okamura; Akihiro Shimizu; Kunihiro Ogawa; et al. (Nuclear Materials and Energy)
This study employs first-principles calculations to investigate the structural, electronic, and mechanical properties of La1-xMxB6 (M = Ba, Sr, Ca), focusing on the surface work function, elastic constants, bulk modulus, shear modulus, Young’s modulus, Debye temperature, and melting point. The results indicate that doping generally leads to a reduction in the surface work function, with La0.375Ba0.625B6 achieving a work function as low as 1.27 eV. The influence of doping concentration on the mechanical properties and anisotropy is analyzed, revealing that La1-xMxB6 and La0.5Sr0.5B6 exhibit oscillatory changes related to the layered structure of the dopants. Brittleness is assessed through the B/G ratio and Poisson’s ratio. Thermodynamic analysis shows that the melting points of these compounds exceed 2000 K. These findings provide useful references for choosing cesium-free electrode materials applied for plasma-facing applications in neutral beam injection.